Low-Complexity Decoding Algorithms for Distributed Space-Time Coded Regenerative Relay Systems - Chao Zhang; Huarui Yin (International Journal of Distributed Sensor Networks, 2012)
We examine decoding structure for distributed space-time coded regenerative relay networks. Given the possible demodulation error at the regenerative relays, we provide a general framework of error aware decoder, where the receiver exploits the demodulation error probability of relays to improve the system performance. Considering the high computational complexity of optimal Maximum Likelihood (ML) decoder, we also propose two low-complexity decoders, Max-Log decoder and Max-Log-Sphere decoder. Computational complexities of these three decoders are also analyzed. Simulation results show that error aware decoders can improve system performance greatly without high system overload and Max-Log decoder and Max-Log-Sphere decoder can drastically reduce the decoding complexity with negligible performance degradation.